A4NH 2019 annual report highlights: Flagship 3 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
This includes three highlights document for Flagship 3 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Supporting international developments in food safety with quality research, engagement Highlight 2: Proving efficacy of Nigeria's aflatoxin biocontrol product: Results from a ten-year study Highlight 3: African food safety index launched